DC-DC Boost Converter Design With Analog Feedback Control for Cryogenic Applications - Danilo Santoro; Niccolo Gallice; Marco Bassani; Paolo Cova; Nicola Delmonte; Massimo Lazzaroni; Valeria Trabattoni; Andrea Zani (IEEE Access)
To bias Silicon PhotoMultiplier (SiPM) sensors, which are used for the readout of scintillation light at cryogenic temperatures, it is essential to develop power supply units that provide stable voltages and low noise. In modern particle physics experiments, these systems may be placed outside the time projection chambers, which are filled with liquid argon (LAr) due to its scintillation properties. However, in the Deep Underground Neutrino Experiment (DUNE) Vertical Drift design, the Photon Detection System (PDS) electronic readout and bias circuits and sensors must be installed on the cathode plane, which is biased at a high DC voltage (-300 kV). Therefore, it is not possible to make any electrical connections between the SiPM and the external interface. Instead, the power is provided through optical fibers using Power over Fiber (PoF) technology. However, the output voltage of these systems is only a few volts and varies in relation to the required current. This paper proposes a 1-to-10 step-up converter solution that operates at cryogenic temperatures to obtain a stable and very low noise 48 V output supply voltage for the SiPM. The design of the converter is based on a boost DC-DC topology, where the components have been selected and characterized to function at cryogenic temperatures. The converter control relies on a type III compensator analog feedback control loop. Simulations and experimental results of a converter prototype, along with the sizing of the control circuit, are presented in this paper.